Extramedullary Solitary Plasmacytoma with Anaplastic Features of the Nasopharynx - Parikshit Padhi; Radwa El-Behery (Case Reports in Hematology)
Extramedullary plasmacytomas (ESPs) are rare forms of plasma cell dyscrasias and usually are seen in the upper aerodigestive tract. ESPs with anaplastic features are extremely rare, and no treatment guidelines exist. We present a 75-year-old gentleman presented with left nasal blockage, and on examination, a polypoid left nasal mass was seen. He was, then, referred to ENT after a CT scan revealed a mass in the left nasopharynx for a biopsy. The preliminary reports suggested a high-grade lymphoma; however, after further testing, it was revealed to be an anaplastic plasma cell neoplasm. PET scan, bone marrow biopsy, serum and urine protein electropheresis, serum immunofixation and light chains were all unremarkable for systemic disease. Differential diagnosis included plasmablastic lymphoma, NK/T cell lymphoma-nasal type, and squamous cell cancers of the head and neck. He was treated with radiation alone given his comorbidities. Given there are no treatment guidelines, we would like to highlight this rare case and discuss different potential management options such as radiation, chemotherapy, surgery, or a combination of different modalities.